2022
DOI: 10.3390/ijms231911330
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Morphological Characteristics of the De-Obstructed Rat Urinary Bladder—An Update

Abstract: Many patients with outlet obstruction secondary to prostatic enlargement have lower urinary tract symptoms (LUTSs) and an increased frequency of micturition. The standard treatment is transurethral resection of the prostate (TURP), which alleviates obstruction and symptoms. However, after TURP, 20–40 percent of patients continue to experience LUTSs. The aim of the present study in rats was to identify the mechanisms that do not normalize after the removal of the obstruction and that could explain the persistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…7 In our current study, we have demonstrated an increased in bladder weight, muscle hypertrophy, and the predominance collagen content in which is consistent with the ndings of other researchs. 2,14,22 Few studies demonstrated the presence of ICCs in the OAB of animal model. 15,16 In the current study we demonstrated the expression of c-kit immunoreactive interstitial cells of Cajal in the BOO rat model compared to the normal control.…”
Section: Discussionmentioning
confidence: 99%
“…7 In our current study, we have demonstrated an increased in bladder weight, muscle hypertrophy, and the predominance collagen content in which is consistent with the ndings of other researchs. 2,14,22 Few studies demonstrated the presence of ICCs in the OAB of animal model. 15,16 In the current study we demonstrated the expression of c-kit immunoreactive interstitial cells of Cajal in the BOO rat model compared to the normal control.…”
Section: Discussionmentioning
confidence: 99%
“…These arrays have been used to characterize what happens at the molecular level during the growth of the obstructed bladder or denervated bladder and to check, in a systematic manner, the effect of obstruction and denervation for the mRNA expression of around 15,000 proteins. The microarrays have been used in other publications [ 3 , 12 , 13 ] and are publicly available (GEO accession numbers GSE47080 and 104540).…”
Section: Methodsmentioning
confidence: 99%
“…Array data show that the hypertrophic response to denervation and obstruction are quite similar. One example is that the messenger RNA (mRNA) for the gap junction protein connexin 43 increases in both (by 2.63 in 10-day obstructed bladder, and by 3.30 in 10-day denervated bladder) [ 3 ]. An increased number of connexons between the smooth muscle cells might be a compensatory mechanism counteracting the decrease or absence of motor nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is possible to monitor both the functional and molecular changes in the bladder after surgical de-obstruction, and this was done in a number of animal studies, mostly in larger rodents such as rats [ 8 , 9 ], guinea pigs [ 10 ] and rabbits [ 11 ]. It was noted that despite the overall improvement of the micturition parameters, complete restoration of bladder function did not occur [ 12 ], and many molecular changes persisted after the relief of obstruction in animals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%